Spirostanol Saponins from Flowers of Allium Porrum and Related Compounds Indicating Cytotoxic Activity and Affecting Nitric Oxide Production Inhibitory Effect in Peritoneal Macrophages - Harmatha, Juraj; Buděšínský, Miloš; Zídek, Zdeněk; Kmoníčková, Eva (Molecules (Basel, Switzerland), 2021)
Saponins, a diverse group of natural compounds, offer an interesting pool of derivatives with biomedical application. In this study, three structurally related spirostanol saponins were isolated and identified from the leek flowers of Allium porrum L. (garden leek). Two of them were identical with the already known leek plant constituents: aginoside (1) and 6-deoxyaginoside (2). The third one was identified as new component of A. porrum; however, it was found identical with yayoisaponin A (3) obtained earlier from a mutant of elephant garlic Allium ampeloprasun L. It is a derivative of the aginoside (1) with additional glucose in its glycosidic chain, identified by MS and NMR analysis as (2α, 3β, 6β, 25R)-2,6-dihydroxyspirostan-3-yl β-D-glucopyranosyl-(1 → 3)-β-D-glucopranosyl-(1 → 2)-[β-D-xylopyranosyl-(1 → 3)]-β-D-glucopyranosyl]-(1 → 4)-β-D-galactopyranoside, previously reported also under the name alliporin. The leek native saponins were tested together with other known and structurally related saponins (tomatonin and digitonin) and with their related aglycones (agigenin and diosgenin) for in vitro cytotoxicity and for effects on NO production in mouse peritoneal cells. The highest inhibitory effects were exhibited by 6-deoxyaginoside. The obtained toxicity data, however, closely correlated with the suppression of NO production. Therefore, an unambiguous linking of obtained bioactivities of saponins with their expected immunobiological properties remained uncertain.
Keywords: Cell Survival; molekulární konformace; Molecular Conformation; peritoneální makrofágy; saponiny; lipopolysacharidy; steroid saponins; Allium porrum; Allium; Lipopolysaccharides; oxid dusnatý; spirostany; zvířata; Nitric Oxide; myši; myši inbrední C57BL; Macrophages, Peritoneal; Mice; Saponins; buněčné linie; Spirostans; alliporin; Cell Line; Mice, Inbred C57BL; Flowers; aginoside; květy; cytotoxicity; Animals; NO production; viabilita buněk; leek flowers